Excavations at Balgonie Castle, Markinch, Fife (Proceedings of the Society of Antiquaries of Scotland, 1996)
Reports excavations in the courtyard area, including details of: `The modern pottery' by G Cruickshank & R S Will (1114); `The clay pipes' by C J M Martin (1116); `Glass' by K R Murdoch (1116--17); and `Animal bones' by Catherine Smith & G W Ian Hodgson (1117).